Sustainable development and geospatial information: a strategic framework for integrating a global policy agenda into national geospatial capabilities. Issue 2 (3rd April 2017) - Scott, Greg; Rajabifard, Abbas
Abstract: The 2030 Agenda for Sustainable Development provides a new global policy to guide the way countries collectively manage and transform the social, economic, and environmental dimensions of people and the planet over the next 15 years. Achieving sustainable development presents all countries and the global policy community with a set of significant development challenges that are almost entirely geographic in nature. Many of the issues impacting sustainable development can be analyzed, modeled, and mapped within a geographic context, which in turn can provide the integrative framework necessary for global collaboration, consensus and evidence-based decision-making. However, and despite significant advances in geospatial information technologies, there is a lack of awareness, understanding and uptake, particular at the policy and decision-making level, of the vital and integrative role of geospatial information and related enabling architectures such as National Spatial Data Infrastructures. This paper reasons that the role of geospatial information in contributing to sustainable development has not adequately been described by either the sustainable development policy practice or by the geospatial professional community. This lack of policy and guidance, with commensurate critical gaps and connection points with national geospatial frameworks, is a visible impediment to developing countries and those most affected by the challenges and need to achieve sustainable development. The global geospatial community now has a unique opportunity to integrate and connect geospatial information into the global development agenda in a more holistic and sustainable manner, specifically in contributing their data resources toward measuring and monitoring the 17 Sustainable Development Goals, and their 169 associated targets, through the global indicator framework that anchors the 2030 Agenda for Sustainable Development. This paper introduces and discusses a new strategic framework for linking a global policy to national geospatial capabilities.